Custom Presurgical Planning for Midfacial Reconstruction - Seim, Nolan B.; Ozer, Enver; Valentin, Sasha; Agrawal, Amit; VanPutten, Mead; Kang, Stephen Y.; Old, Matthew O. (Facial Plastic Surgery, 2020)
Resection and reconstruction of midface involve complex ablative and reconstructive tools in head and oncology and maxillofacial prosthodontics. This region is extraordinarily important for long-term aesthetic and functional performance. From a reconstructive standpoint, this region has always been known to present challenges to a reconstructive surgeon due to the complex three-dimensional anatomy, the variable defects created, combination of the medical and dental functionalities, and the distance from reliable donor vessels for free tissue transfer. Another challenge one faces is the unique features of each individual resection defect as well as individual patient factors making each preoperative planning session and reconstruction unique. Understanding the long-term effects on speech, swallowing, and vision, one should routinely utilize a multidisciplinary approach to resection and reconstruction, including head and neck reconstructive surgeons, prosthodontists, speech language pathologists, oculoplastic surgeons, dentists, and/or craniofacial teams as indicated and with each practice pattern. With this in mind, we present our planning and reconstructive algorithm in midface reconstruction, including a dedicated focus on dental rehabilitation via custom presurgical planning.
Keywords: medical modeling; midface reconstruction; maxillectomy; dental rehabilitation; free tissue transfer; osseointegrated implants